2011
DOI: 10.4240/wjgs.v3.i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery programs hasten recovery after colorectal resections

Abstract: Colorectal resection was traditionally associated with significant morbidity and prolonged stay in hospital. Laparoscopic colorectal resection was first described in 1991 as a minimally invasive form of colorectal surgery. It was later on assessed by multiple randomized controlled trials and meta-analysis and was found to be associated with a faster recovery, lower complication rates and a shorter stay in hospital compared with open resection. To assess the effect of enhanced recovery after surgery (ERAS) prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 35 publications
0
17
0
8
Order By: Relevance
“…ERAS principles have long been established in elective major abdominal surgical patients . From the first descriptions in colonic surgery, there has been ‘diffusion’ or ‘metastasis’ to rectal surgery and other specialities .…”
Section: Discussionmentioning
confidence: 99%
“…ERAS principles have long been established in elective major abdominal surgical patients . From the first descriptions in colonic surgery, there has been ‘diffusion’ or ‘metastasis’ to rectal surgery and other specialities .…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent larger studies reported a median length of stay of about five days, three days longer than what was reported in the first series (Abraham & Albayati, 2011;Nygren et al, 2009). Multiple published trials and systematic reviews have reported that ERAS protocols were associated with a faster recovery, reduced primary and overall lengths of hospital stay and complication rates after colorectal resections compared with the traditional approach.…”
Section: Supportive Evidence For Eras Protocolsmentioning
confidence: 76%
“…In 1999, in a series of 16 open colectomies, the authors reported using a Fast Track (Enhanced Recovery after Surgery (ERAS)) Program with a median postoperative length of hospital stay of two days (Kehlet & Mogensen, 1999). However, subsequent larger studies reported a median length of stay of about five days (Abraham & Albayati, 2011). ERAS programs challenge the conventional approaches to peri-operative care in colorectal surgery in an evidence-based manner.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, в этих группах не вы-явлено различий объема желудочного содержимого и его рН [8]. Это мнение было подтверждено в по-следующих публикациях [6]. В настоящий момент рекомендации ERAS предусматривают прекраще-ние приема твердой пищи за 6 ч до операции, а жид-костей -за 2 ч [15].…”
Section: предоперационная стратегияunclassified